Apoyo en área técnica para la formulación y/o supervisión de proyectos en la empresa servicios especializados profesionales integrales limitada de la ciudad de Tunja (2022)
The following work was carried out under the modality of internship in the company comprehensive professional specialized services limited. SEPI LTDA, located in the city of Tunja Boyacá, which carries out design projects, study, construction, contracting, and subcontracting of civil works. It is currently carrying out the construction of the Hogar Vida, and the reconstruction and improvement of the house of culture i the internship is being carried out. n the municipality of Toca Boyacá, projects in which The internship includes two projects in which the intern performs engineering assistant roles, as follows: The reconstruction and improvement project of the house of culture is comprised of two floors. In which the first floor consists of an auditorium, Vestier rooms, bathrooms, patio area, has stairs to access the second floor where it consists of storage rooms, staff service offices and bathrooms. The home life proje ct is also on two floors with an area of 563.9 m2. In which the first floor consists of a kitchen, dining room, bathrooms, office, patio area, waste area and has an elevator to access the second floor where it consists of a gym, bathrooms, multiple class service office and has stairs for first level access. , , construction rooms,